2004
DOI: 10.1016/j.cardiores.2003.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-based prostacyclin synthase gene transfer prevents in-stent restenosis in rabbit atheromatous arteries

Abstract: PGIS gene transfer accelerated re-endothelialization, and attenuated neointimal formation after stent implantation in atheromatous rabbit arteries, at least in part, via increased production of VEGF protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 38 publications
1
27
0
1
Order By: Relevance
“…40 The proliferation index of glomeruli of Tg rabbits was compared with that of control rabbits at 40 wk. BrdU (50 mg/kg) was subcutaneously injected at 1,8,16, and 24 h before the removal of the kidney.…”
Section: Proliferation Index In Glomerulusmentioning
confidence: 99%
“…40 The proliferation index of glomeruli of Tg rabbits was compared with that of control rabbits at 40 wk. BrdU (50 mg/kg) was subcutaneously injected at 1,8,16, and 24 h before the removal of the kidney.…”
Section: Proliferation Index In Glomerulusmentioning
confidence: 99%
“…Индуцированная экспрессия VEGF приводи-ла к росту и восстановлению эндотелия сосудов после повреждения. Также было показано, что по-вышение экспрессии гена простациклин-синтазы ускоряет реэндотелиализацию и предотвращает образования неоинтимы в травмированных баллоном артериях в предклинической модели [56]. Тем не менее этот эффект был замечен в со-четании с доставкой гена VEGF и вполне может быть связан с более поздней трансдукцией гена.…”
Section: гены стимулирующие реэндотелиализациюunclassified
“…Gene transfer of PGI 2 synthase has also been shown to accelerate re-endothelialization and prevent neointimal formation in balloon-injured arteries. In a rabbit model, PGI 2 synthase gene delivery by the lipotransfection method via dispatch catheter can accelerate re-endothelialization and attenuate neointimal formation (36). Douglas et al (20) found that endothelial-specific overexpression of GTP-cyclohydrolase-1 can enhance endothelial cell function and increases NO production, thus promoting re-endothelialization after stent deployment.…”
Section: Evolution Of Antirestenosis Therapymentioning
confidence: 99%
“…Takemoto et al (60) found that transfection of the human pE-NTPDase gene, encoding an enzyme that rapidly hydrolyzes ATP and ADP to AMP via cationic gelatin-coated stents, inhibits subacute in-stent thrombosis and suppresses neointimal hyperplasia and inflammation without antiplatelet drugs. More established antithrombotic genes, including PGI 2 synthase, COX-1 and tissue factor pathway inhibitor, have been investigated in recent years for their potential in postangioplasty intervention, and have demonstrated successful suppression of thrombosis and/or restenosis in various animal models (34,36,58,61).…”
Section: Anti-inflammationmentioning
confidence: 99%